Rational design and modular synthesis of biodegradable ionizable lipids via the Passerini reaction for mRNA delivery - Yue Xu; Fanglin Gong; Alex Golubovic; Amy Strilchuk; Jingan Chen; Muye Zhou; Songtao Dong; Breanna Seto; Bowen Li (Proceedings of the National Academy of Sciences, 2025)
The ionizable lipid component of lipid nanoparticle (LNP) formulations is essential for mRNA delivery by facilitating endosomal escape. Conventionally, these lipids are synthesized through complex, multistep chemical processes that are both time-consuming and require significant engineering. Furthermore, the development of new ionizable lipids is hindered by a limited understanding of the structure-activity relationships essential for effective mRNA delivery. In this work, we have developed a modular platform utilizing the Passerini reaction to rapidly generate large, chemically diverse libraries of biodegradable ionizable lipids. This high-throughput approach enables the systematic exploration of various lipid components–head groups, tails, and spacers–and their impacts on mRNA delivery efficiency. By investigating the hydrogen bonding potential between the lipid’s head groups and the mRNA’s ribose phosphate complex, we found that optimizing the methylene units between the lipid’s head groups and linkages could enhance endosomal escape and, consequently, mRNA delivery efficiencies. Leveraging this insight, our platform has led to the identification of the biodegradable ionizable lipid A4B4-S3, which outperforms the current clinical benchmark, SM-102, in gene editing efficacy in mouse liver following systemic administration and demonstrates the promise for repeat-dose protein replacement treatments. This work not only offers a rapid, scalable method for ionizable lipid synthesis but also deepens our understanding of their structure-activity relationships, paving the way for more effective mRNA therapeutics.